The Effect Of Training Using Hand Paddle Aids On 15 Metre Freestyle Swimming Speed In Swimmers At Spc Swimming Club - Valent, Muhammad Kelvin; Astuty, Lina Try; Martiani, Martiani (Utami Publisher, 2025)
This study aims to determine the effect of hand paddle training on 15 metre freestyle swimming speed in swimmers at SPC Swimming Club. This type of research is quantitative research. The research sample totalled 20 people. The instrument used in this study was a freestyle swimming speed test using the Hand Paddle training method. Where the results of the study can be seen an increase from the initial pretest to the posttest, this can be seen from the numbers obtained from the results of the study where for the pretest value as many as 10 people (50%) had a category of less and for the posttest as many as 12 people (60%) had a sufficient category, meaning that the results of the study can be said to have increased significantly.